2001
DOI: 10.1007/s007050170122
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant proteins produced by vaccinia virus vectors can be incorporated within the virion (IMV form) into different compartments

Abstract: Vaccinia virus (VV) is one of the largest and most complex of animal viruses, with a virion that contains about 100 different polypeptides. Assembly of the viral proteins occurs in discrete cytoplasmic sites leading to formation of two infectious forms, an abundant (>90%) intracellular mature virus (IMV) with an envelope, and a minor extracellular enveloped virus (EEV) with an extra membrane acquired from the trans-Golgi network. It has been shown that while EEV contains in the outer membrane cellular proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Interestingly, neither G5 nor G6 have been identified in any of the published proteomic studies. Because in these studies G5 and G6 were expressed under a T7 operator it is possible that under these conditions both proteins were overexpressed and passively encapsidated by the virions (Franke and Hruby, 1987; Gomez and Esteban, 2001). We showed that the treatment of cores with higher a concentration of 100 mM DTT and 3M NaCl could remove proteins from the surface of the core while preserving its structure.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, neither G5 nor G6 have been identified in any of the published proteomic studies. Because in these studies G5 and G6 were expressed under a T7 operator it is possible that under these conditions both proteins were overexpressed and passively encapsidated by the virions (Franke and Hruby, 1987; Gomez and Esteban, 2001). We showed that the treatment of cores with higher a concentration of 100 mM DTT and 3M NaCl could remove proteins from the surface of the core while preserving its structure.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccinia virus expressing the bacterial CAT gene incorporated the enzyme into the virus particle [46]. The expression of the cytokine IL-12 led to the incorporation of about 0.01% of the total recombinant protein into an envelope fraction, HIV1 env (gp160-120) was tightly bound in protein-DNA complexes, and the enzyme beta-galactosidase was found exclusively in core-associated fraction [47]. Transport and sorting of viral proteins directly from the endoplasmic reticulum into the growing immature virions using non-COPII vesicles [48] could explain selective integration of the low-glycosylated FL into P13-E/L-FL virions.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is not unexpected, particularly with recent evidence suggesting that intracellular expression of proteins from rVV transgenes often leads to incorporation of these proteins in both EEV and the more prevalent intracellular mature virion (IMV) particles. 25,26 Moreover, it has been shown that proteins originating from host cells and carried by the virus might be biologically active as exemplified by retroviral vectors produced in FasL-expressing cell lines. 39 The differences in IL-12 synthesis in DC exposed to replicating or nonreplicating rV-CD40L, or to MC38 cells infected with either of the viruses, indicate that the biologic effect of rV-CD40L is difficult to predict and likely depends on the diverse effects of CD40L protein carried by the viral particles, intracellular expression of CD40L and the adjuvant properties as well as cytopathic effects of the viral vector.…”
Section: Dx5 þ (Nk/nkt) Cells Proliferate and Release Ifn-g In Responmentioning
confidence: 99%
“…23,24 Viral immunogenicity may also be influenced by cellular antigens that are carried by VV particles acquired from host cells in culture. 25,26 This occurs due to the life cycle of VV within the cytoplasm of infected cells, where intracellular membranes are incorporated into intracellular enveloped virus (IEV) or cell membrane components are captured by the virus during assembly of extracellular enveloped virus (EEV) particles. The immunologic consequences of these ''captured proteins'' have not been fully elucidated in vaccination models, but could theoretically influence the quality of the immune response.…”
mentioning
confidence: 99%